Cost‐of‐illness of atopic dermatitis in Germany: data from dermatology routine care. (7th May 2021) - Mohr, N.; Naatz, M.; Zeervi, L.; Langenbruch, A.; Bieber, T.; Werfel, T.; Wollenberg, A.; Augustin, M.
Abstract: Background: Progress in the management of atopic dermatitis (AD) and the recent introduction of the first biologic have raised interest in the costs of treating AD. Objectives: Since there is a lack of recent data, the objective of this study was to determine the annual costs of adults with AD from the societal perspective. Methods: A nationwide cross‐sectional study was conducted in 111 dermatological offices under routine conditions. Cost parameters were collected with a standardised questionnaire on disease‐related costs. This questionnaire allows the determination of costs for systemic and topical treatment, outpatient and inpatient visits, rehabilitation stays and travel costs. Direct costs were determined for the statutory health insurance (SHI) and for the patients (out‐of‐pocket costs). Societal costs also included the indirect costs due to incapacity to work. Costs were calculated for all severity grades and further stratified by mild and moderate‐to‐severe AD. Results: From August 2017 to June 2019, N = 1291 adult patients from all over Germany were included. The total annual costs in the group with all severity grades ( n = 706) amounted to € 3616 ± € 6452 (median € 874) per patient. For patients with mild AD ( n = 367), the annual costs were € 1466 ± € 3029 (median € 551) per patient, while they were € 5229 ± € 7538 (median € 1791) for patients with moderate‐to‐severe AD ( n = 682). The total economic burden for treating adult patients with AD in Germany is estimated at more than € 2.2 billion. Conclusions: In total, the data from this study show that compared to for example psoriasis, AD has a moderate level of costs‐of‐illness in Germany. The approval of new therapies is expected to lead to markedly more resource utilisation in the next years.